Ignorance and change : anticipatory knowledge and the European refugee crisis /: anticipatory knowledge and the European refugee crisis. (2020) - Mica, Adriana; Horolets, Anna; Pawlak, Mikołaj; Kubicki, Paweł
No abstract available